Reactive sintering of yttrium-doped barium zirconate (BaZr0.8Y0.2O3-δ) without sintering aids - Goulart, Celso Antonio; Villas-Boas, Lúcia Adriana [UNESP]; Morelli, Márcio Raymundo; Souza, Dulcina Pinatti Ferreira de (Elsevier, 2021)
The effects of Yttrium-doped Barium Zirconate (BZY) synthesis steps by solid-state reaction and the number of starting reactants (2 or 3) on the characteristics of the synthesized ceramic powders were investigated. The slow diffusion rate associated with this synthesis route and the calcination steps used in this work lead to an incomplete synthesis reaction. This condition proved to be useful to improve densification during sintering for undoped samples by emulating the reactive sintering technique with transient reactions originating from the residual BaCO3 reactant. The effects of a low concentration (1 mol%) of ZnO as sintering aid on microstructure and electrical conductivity were also investigated and used for comparison to undoped samples. Electrical properties were analyzed and correlated with microstructural and compositional characteristics. Dense undoped BZY samples (99% of relative density) with high proton conductivity (2.4×10−2S/cm at 600 °C) were obtained by sintering at 1500 °C, while ZnO-doped samples achieved high relative density (97%) at only 1300 °C, but with lower electrical conductivity (7.8×10−3 S/cm at 600 °C).
Keywords: Ceramic processing; PCFC; Protonic conductivity; Solid-state reaction; Yttrium-doped barium zirconate